Enforced ATP futile cycling increases specific productivity and yield of anaerobic lactate production in Escherichia coli. Issue 10 (30th June 2015) - Hädicke, Oliver; Bettenbrock, Katja; Klamt, Steffen
ABSTRACT The manipulation of cofactor pools such as ATP or NAD(P)H has for long been recognized as key targets for metabolic engineering of microorganisms to improve yields and productivities of biotechnological processes. Several works in the past have shown that enforcing ATP futile cycling may enhance the synthesis of certain products under aerobic conditions. However, case studies demonstrating that ATP wasting may also have beneficial effects for anaerobic production processes are scarce. Taking lactic acid as an economically relevant product, we demonstrate that induction of ATP futile cycling in Escherichia coli leads to increased yields and specific production rates under anaerobic conditions, even in the case where lactate is already produced with high yields. Specifically, we constructed a high lactate producer strain KBM10111 (= MG1655 ΔadhE::Cam ΔackA‐pta) and implemented an IPTG‐inducible overexpression of ppsA encoding for PEP synthase which, together with pyruvate kinase, gives rise to an ATP consuming cycle. Under induction of ppsA, KBM10111 exhibits a 25% higher specific lactate productivity as well as an 8% higher lactate yield. Furthermore, the specific substrate uptake rate was increased by 14%. However, trade‐offs between specific and volumetric productivities must be considered when ATP wasting strategies are used to shift substrate conversion from biomass to product synthesis and we discuss potential solutions to design optimal processes. In summary, enforced ATP futile cycling has great potential to optimize a variety of production processes and our study demonstrates that this holds true also for anaerobic processes. Biotechnol. Bioeng. 2015;112: 2195–2199. © 2015 Wiley Periodicals, Inc.